Aymé–Gripp syndrome in a Russian patient with a newly detected mutation in the MAF gene - E. L. Dadali; T. V. Markova; O. P. Ryzhkova (Нервно-мышечные болезни)
Aymé–Gripp syndrome is a rare autosomal dominant syndrome caused by mutations in the MAF gene and is characterized by a pronounced phenotypic polymorphism. The core of clinical signs consists of congenital cataracts, sensorineural hearing loss, specific dysmorphic facial features and intellectual disabilities. With varying frequency, patients have: radioulnar synostosis, Arnold–Chiari malformation, aseptic pericarditis, dental anomaly and osteoarthritis. The article presents the clinical and genetic characteristics of the first Russian patient with Aymé–Gripp syndrome caused by a newly identified mutation s.173C>A (p.Thr58Asn NM_005360.4) in a heterozygous state in the MAF gene. The influence of the lo  calization and type of amino acid substitutions in the protein product of the gene on the severity and specificity of the clinical manifestations of the syndrome is discussed.